The Effect of Gamification-Based Online Learning on Student Learning Outcomes - Asriadi; M. Miftach Fakhri; Jumadil Ahmad Safi’i; Muh. Alif; Della Fadhilatunisa (Jurusan Teknik Informatika dan Komputer, 2024)
New things are starting to emerge that were not previously considered due to the COVID-19 pandemic, one of which is the shift to online learning. The low level of student participation during the pandemic is a global issue, not limited to Indonesia. One approach that can be used to address this issue is the gamification of online learning. The learning outcomes are essentially the measurement of students' success and achievements in the learning process. Therefore, the relationship between the gamification approach and learning outcomes in online education is a phenomenon that we can understand and further examine. This research is of a quantitative nature with a descriptive research design (data collection, analysis, and presentation). The population and sample are active enrolled students, and the data is collected widely online. The instrument used is a research questionnaire with the data collection technique involving the analysis of questionnaire responses distributed through Google Forms, using a Likert scale model ranging from very positive to very negative. Descriptive techniques involve statistical and correlational methods. The abundance of responses from students indicates that gamified online learning has the potential to significantly influence students' learning outcomes.